A note on differences of composition operators acting on the Hardy space - Dai, Jineng (MATHEMATICA SCANDINAVICA, 2022)
When φ and ψ are holomorphic self-maps of the unit disk with bounded multiplicity, we give a compact characterization for the difference of composition operators C_φ and C_ψ acting on the Hardy space, which extends a recent result in the case of univalent maps by Choe et al.